The Role of the Assurance Dimension of Sustainability Reporting on Greenwashing: Systematic Literature Review - Handani, Riska; Djaddang, Syahril (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The practice of sustainability assurance has rapidly expanded in response to growing demands for transparency and accountability in environmental, social, and governance (ESG) domains. However, the effectiveness of assurance in mitigating greenwashing remains debated. This study systematically reviews recent empirical findings on the influence of four assurance dimensions—existence, provider, level, and scope—on greenwashing. A Systematic Literature Review (SLR) approach guided by PRISMA was applied to 20 peer-reviewed articles published between 2020 and 2025 across various countries and industry sectors. The synthesis reveals that assurance enhances stakeholder trust, promotes transparency, and improves market perceptions of corporate responsibility and governance when implemented under high-quality conditions. Nevertheless, its effectiveness largely depends on the independence of the assurance provider, the level of assurance obtained, and the comprehensiveness of the report’s scope. Limited assurance or that conducted by non-accounting providers tends to be symbolic, whereas comprehensive assurance with broader coverage is more substantive in reducing the gap between disclosure and actual sustainability performance. This study highlights the importance of improving assurance quality and harmonizing assurance practices as a governance mechanism to mitigate the risk of greenwashing in sustainability reporting, contributing to the growing discourse on credibility and legitimacy in ESG disclosure.